Open-ended laboratory: comprehensive course evaluation framework for structural engineering laboratory / Mohd Samsudin Abdul Hamid and Noor Syafeekha Mohamad Sakdun - Abdul Hamid, Mohd Samsudin; Mohamad Sakdun, Noor Syafeekha (Universiti Teknologi MARA, Perlis, 2024)
Comprehensive course evaluation is important to provide better performance of teaching and learning assessment. In higher learning education for engineering laboratory subjects, the requirement of evaluation provides complicated criteria where it needs to fulfill Outcome-based Education, Openended Laboratory and Complex Engineering Problems. Previously, the laboratory course was conducted through fully guided assignments by using too many separate evaluation guidelines and rubrics; thus, it became difficult to keep track each assessment tool and openness level which led to complication and confusion to the students. A misunderstanding process on the mapping of the criteria always occurs which contributes to the misleading of domain evaluation for each course. Therefore, this study was developed to design a comprehensive course evaluation framework for open-ended laboratory subjects by using educational and accreditation guidelines. EAC, UHEK and OEL guidelines were referred to as a comprehensive reference in developing the teaching and learning mechanism for each course developed in UiTM. Six main stages from the gathering of course information to the development of comprehensive rubrics should be carefully defined to ensure holistic framework is provided in this study. It was found that the framework provides clear mapping of the three main criteria developed as guidelines for the evaluation process in engineering laboratory subject. Besides that, it gives an objective evaluation criterion that meets the difficulty level of the subject with respect to OBE, OEL and CEP. The framework is able to be implemented in all subjects either engineering or non-engineering by mapping each evaluation criteria based on the nature of the subjects.